GPC3 reduces cell proliferation in renal carcinoma cell lines - Valsechi, Marina Curado [UNESP]; Bortolozo Oliveira, Ana Beatriz [UNESP]; Giacometti Conceicao, Andre Luis [UNESP]; Stuqui, Bruna [UNESP]; Candido, Natalia Maria [UNESP]; Scarin Provazzi, Paola Jocelan [UNESP]; Araujo, Luiza Ferreira de; Silva, Wilson Araujo; Calmon, Marilia de Freitas [UNESP]; Rahal, Paula [UNESP] (Biomed Central Ltd, 2014)
Background: Glypican 3 (GPC3) is a member of the family of glypican heparan sulfate proteoglycans (HSPGs). The GPC3 gene may play a role in controlling cell migration, negatively regulating cell growth and inducing apoptosis. GPC3 is downregulated in several cancers, which can result in uncontrolled cell growth and can also contribute to the malignant phenotype of some tumors. The purpose of this study was to analyze the mechanism of action of the GPC3 gene in clear cell renal cell carcinoma.Methods: Five clear cell renal cell carcinoma cell lines and carcinoma samples were used to analyze GPC3 mRNA expression (qRT-PCR). Then, representative cell lines, one primary renal carcinoma (786-O) and one metastatic renal carcinoma (ACHN), were chosen to carry out functional studies. We constructed a GPC3 expression vector and transfected the renal carcinoma cell lines, 786-O and ACHN. GPC3 overexpression was analyzed using qRT-PCR and immunocytochemistry. We evaluated cell proliferation using MTT and colony formation assays. Flow cytometry was used to evaluate apoptosis and perform cell cycle analyses.Results: We observed that GPC3 is downregulated in clear cell renal cell carcinoma samples and cell lines compared with normal renal samples. GPC3 mRNA expression and protein levels in 786-O and ACHN cell lines increased after transfection with the GPC3 expression construct, and the cell proliferation rate decreased in both cell lines following overexpression of GPC3. Further, apoptosis was not induced in the renal cell carcinoma cell lines overexpressing GPC3, and there was an increase in the cell population during the G1 phase in the cell cycle.Conclusion: We suggest that the GPC3 gene reduces the rate of cell proliferation through cell cycle arrest during the G1 phase in renal cell carcinoma.
Keywords: GPC3; Cell lines; Cell proliferation; Renal carcinoma; Transfection